The Burgeoning Securities Investment Fund Industry in China: Its Development and Regulation - Tao, Tingting (Columbia Journal of Asian Law, 1999)
The first investment fund in China was born in 1991. Despite this late start, China’s investment funds have grown rapidly, and their number and size are expected to expand greatly in the coming years. The funds have developed in two stages demarcated by the national regulation promulgated in 1997. Before that time, funds were at the stage of self-development. A total of 75 funds and 47 fund-like certificates had been launched with the accumulated capital of more than Renminbi (“RMB”) 7 billion yuan (approximately US 1 = RMB 8.3 yuan as of September 1999). These funds are often referred to as “old funds,” as opposed to the new funds established after the national regulation. The old funds introduced the concept of the investment fund into China and led the Chinese to realize their potential as instruments for investment. The small size of the old funds, however, made them unable to play a significant role in China’s securities market. Their erratic management and poor risk control also highlighted the necessity of official regulation. The Provisional Measures for the Administration of Securities Investment Funds (“Provisional Measures’), promulgated in November 1997, are the first national regulation governing the domestic fund industry. Under the Provisional Measures, China’s funds began a new era of development, and 14 new funds had been set up with a total capital of RMB 32 billion yuan by the end of July 1999.